Patrimônio e memória: um olhar sobre as paisagens ferroviárias do município de Restinga-Sêca/RS - 1920 até os dias atuais - Alves, Heliana de Moraes (2013)
The railway transportation played an important role in the setting of the spacing and cultural dynamics, because it brought new values and new social practices to the place where it was present, defining innumerous railway landscapes. The railway landscapes are formed by structures and meanings which are part of the city of Restinga Sêca s identity and history, considering that this city developed, in space, from the railroad Porto Alegre Uruguaiana. These landscapes have gone through innumerous modifications since the summit till the railway transportation s fall, in this sense, there is a necessity to understand them thorough the memory which is related to them. Therefore, the objective was to understand how the transformation problems in Restinga Sêca s railway landscapes have set up since 1920 to the present days. For that, it was necessary to investigate how the historical-spacing organization happened in the country s railroad, in a regional approach and as well in the studied city; identify the social spacing aspects and the elements which are part of the railroad memory in the railroad nuclei s landscapes in the city; analyze the fall of the railway transportation and the role changes in the railway equipment; and also understand the representations that the railway landscape has to the memory of the local population. The study was directed to three strategic points in the city, which have social spacing genesis linked to the railway: the city of Restinga Sêca, the locality of Estiva and the locality of Jacuí. Each locality has its railway landscape which gets integrated to each other, setting up the studied city s railway patrimony. It was also necessary to look at the past, not only through the institutionalized official history, but also focus the memory associated to it. With this objective, this research has a qualitative approach based on phenomenological method, because it values the conscience and the experiences lived by each individual in relation to the place. In this slant, it was important to value the railway memory, once it provided conditions for a better understanding of the city s railway landscapes which were being studied, what will contribute for a future proposal of patrimonial preservation.